Prevalence and risk factors for bruxism among climbers - Zięba, Estera; Byś, Aleksandra (Journal of Education, Health and Sport, 2019)
Background: Bruxism is defined as the parafunction of masticatory system, which consists in clamping or gnashing teeth, often combined with the feeling of stiffness of the jaw. Risk factors for bruxism include psychosocial factors e.g. stress and anxiety. Climbing, as a extreme sports, may be associated with an increased level of mental tension due to the relatively high stress load. ¬Aim: This study aims to determine the prevalence and risk factors for bruxism among climbers. Material and methods: 104 people came for the study. Finally 88 people were qualified for the statistical analysis, including 41 women and 47 men with an average age of 28 years (± 7 years). The study consisted of an author's questionnaire containing questions about bruxism and its risk factors. The questions used to assess bruxism were constructed in accordance with the guidelines of Pintado et al., Lavigne et al. and Thorpy. Results: 51.1% of the respondents suffered from awakening bruxism (51.2% women, 51.1% men), while 22.7% suffered from sleep bruxism (34.1% women, 12.8% men). 73.3% of the respondents with awakening bruksizm and 80% of the respondents with sleep bruxism had higher education. Conclusions:• The prevalence of sleep bruxism among climbers is 22.7%, while awake bruxism is 51.1%.• The higher prevalence of bruxism in climbers relative to the general population can be explained by the specificity of the mobility abilities necessary for climbing training and the climber's mental burden.• Both sleep and awake bruxism seems to be associated with higher education.• Sleep bruxism is more common in climbing women than in climbing men.• We recommend further research into the prevalence and risk factors for bruxism among climbers and other athletes.